Patterns of Human Respiratory Viruses and Lack of MERS-Coronavirus in Patients with Acute Upper Respiratory Tract Infections in Southwestern Province of Saudi Arabia - Ahmed A. Abdulhaq (Advances in Virology, 2017)
We undertook enhanced surveillance of those presenting with respiratory symptoms at five healthcare centers by testing all symptomatic outpatients between November 2013 and January 2014 (winter time). Nasal swabs were collected from 182 patients and screened for MERS-CoV as well as other respiratory viruses using RT-PCR and multiplex microarray. A total of 75 (41.2%) of these patients had positive viral infection. MERS-CoV was not detected in any of the samples. Human rhinovirus (hRV) was the most detected pathogen (40.9%) followed by non-MERS-CoV human coronaviruses (19.3%), influenza (Flu) viruses (15.9%), and human respiratory syncytial virus (hRSV) (13.6%). Viruses differed markedly depending on age in which hRV, Flu A, and hCoV-OC43 were more prevalent in adults and RSV, hCoV-HKU1, and hCoV-NL63 were mostly restricted to children under the age of 15. Moreover, coinfection was not uncommon in this study, in which 17.3% of the infected patients had dual infections due to several combinations of viruses. Dual infections decreased with age and completely disappeared in people older than 45 years. Our study confirms that MERS-CoV is not common in the southwestern region of Saudi Arabia and shows high diversity and prevalence of other common respiratory viruses. This study also highlights the importance and contribution of enhanced surveillance systems for better infection control.